Surface roughness optimization of face milling operation using Taguchi design method - Mohd Azmi, Md Juni (2008)
Lately, there are many factories in Malaysia were build and increasing along with the development of the economic structure and national rapid development. However, not all the engineers in those factories are using proper statistical analysis in their research in the industry. Throughout this project which “Surface Roughness Optimization of Face Milling Operation Using Taguchi Design Method”, the result will be analyzed using DOE methodology and software. Implementing DOE method,the experiment is based on L9 Orthogonal Array of Taguchi Design Method experiment. The study is focusing on milling process which one of the cutting process. The experiment is conducted using milling machine and measured using the perthometer equipment. The analysis consists of three main elements which are finding the significant factor, Analysis of Variance (ANOVA) and estimated result at optimum condition. Finally, the outcome of the study is to determine if the DOE methodology can analyze the best surface roughness value and its effectiveness for the statistical analysis.